Biosimilar FSH preparations- are they identical twins or just siblings?. Issue 1 (December 2016) - Orvieto, Raoul; Seifer, David
Abstract As patents expire on innovator products, there is increasing interest in developing biosimilar products globally. Biosimilars are not exact copies and are not considered generic versions of the reference product. They may differ in strength, purity and contain different composition of isoforms and/or various glycosylation profiles, with the consequent alterations in clinical efficacy or safety. Recently 2 new recombinant FSH preparations were introduced to clinical practice following randomized controlled, phase 3 clinical trials. Both, Bemfola and Ovaleap® were referred to the FSH innovator product Gonal-f™ (Follitropin alpha), and were found to yield an equivalent number of oocytes (primary end-point), following a long GnRH agonist suppressive protocol in "ideal" patients, i.e., young, normal responders. However, a closer look at these RCTs reveals a non-significant 4 % difference in clinical and ongoing pregnancy rates, in favor of Gonal f over the biosimilar products, accompanied by half the incidence of OHSS (2.9 vs 5.2 %, respectively). These studies were underpowered with reference to pregnancy rates, Thus, we believe that further comparative studies are needed in additional patient populations, e.g., older, , poor responders, patients with repeated IVF failures and/or polycystic ovary syndrome, before the universal implementation of biosimilar products for clinical use. Biosimilars are actually a regulatory synonym, facilitating a fast track introduction of a FSH preparation to the COH armamentarium. We therefore recommend against interchanging or substituting innovator and biosimilar agents in clinical practice, and believe that the decision whether to use an innovator or a biosimilar product, should be reserved to the discretion of the treating physician. Furthermore, we believe the time has come that the measurement of the biological activity of FSH in humans should require other methods rather than the Steelman-Pohley assay, such as the determination of dose–response curves in defined populations of women with well-defined outcomes during COH in preparation for ART.